Transformation of Sound System Rental Services MSMEs Through Comprehensive Assistance: Case Study of "The Ndee Sound System" - Christianadi, Januar Ika; Winarno, Agung; Hermawan, Agus (Journal of Applied Business, Taxation and Economics Research, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the Indonesian economy; however, many continue to face challenges in business management, particularly in branding, digital marketing, pricing strategies, and operational efficiency. This study aims to analyze the effectiveness of a comprehensive mentoring program implemented for a sound system rental MSME, “The Ndee Sound System,” located in Cikarang. The research adopts a qualitative approach using a case study method. Data were collected through participatory observation, in-depth interviews with the business owner and related parties, documentation review, and competitor analysis. The mentoring program was conducted through five main stages: development of brand identity and digital presence, systematic organization of an equipment portfolio, enhancement of event documentation and customer testimonials, implementation of transparent and structured pricing, and establishment of strategic partnerships with supporting vendors. Each stage was designed to gradually strengthen managerial capacity, improve service quality, and enhance market competitiveness. The results indicate significant improvements in business performance. Monthly revenue increased by 45%, while customer inquiries rose by up to 600%, and the conversion rate reached 25–30%. In addition, operational costs were reduced by approximately 25% through strategic partnerships, and operational readiness improved to 90%. A stronger brand identity and consistent digital presence also contributed to a substantial increase in brand awareness, expanding the business reach from a local to a regional market. This study concludes that a structured and holistic mentoring approach can significantly improve business performance, competitiveness, and long-term sustainability of service-based MSMEs, particularly in the event equipment rental sector.